Re: Endothelial dysfunction and vascular stiffness in women with previous pregnancy complicated by early or late pre‐eclampsia. R. Orabona, E. Sciatti, E. Vizzardi, I. Bonadei and A. Valcamonico. Ultrasound Obstet Gynecol 2017; 49: 116–123. (January 2017) - Morris, E. A.; Bernstein, I. M.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 116–123